GFTT: Geographical Feature Tokenization Transformer for SAR-to-Optical Image Translation - Hongbo Liang; Xuezhi Yang; Xiangyu Yang; Jinjin Luo; Jiajia Zhu (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Synthetic aperture radar (SAR) image to optical image translation not only assists information interpretability, but also fills the gaps in optical applications due to weather and light limitations. However, several studies have pointed out that specialized methods heavily struggle to deliver images with widely varying optical imaging styles, thus, resulting in poor image translation with disharmonious and repetitive artifacts. Another critical issue attributes to the scarcity of geographical prior knowledge. The generator always attempts to produce images within a narrow scope of the data space, which severely restricts the semantic correspondence between SAR content and optical styles. In this article, we introduce a novel tokenization, namely geographical imaging tokenizer (GIT), which captures imaging style of ground materials in the optical image. Based on the GIT, we propose a geographical feature tokenization transformer framework (GFTT) that discovers the consensus between SAR and optical images. In addition, we leverage a self-supervisory task to encourage the transformer to learn meaningful semantic correspondence from local and global style patterns. Finally, we utilize the noise-contrastive estimation loss to maximize mutual information between the input and translated image. Through qualitative and quantitative experimental evaluations, we verify the reliability of the proposed GIT that aligns with authentic expressions of the optical observation scenario, and indicates the superiority of GFTT in contrast to the state-of-the-art algorithms.